Rough Sets and Knowledge Technology 6th International Conference, RSKT 2011, Banff, Canada, October 9-12, 2011. Proceedings - Yao, JingTao; Ramanna, Sheela; Wang, Guoyin; Suraj, Zbigniew; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 6th International Conference on Rough Sets and Knowledge Technology, RSKT 2011, held in Banff, Canada, in September 2011. The 89 revised full papers presented together with 3 keynote lectures and 1 invited tutorial session were carefully reviewed and selected from 229 submissions. The papers are organized in topical sections on attribute reduction and feature selection, generalized rough set models, machine learning with rough and hybrid techniques, knowledge technology and intelligent systems and applications.
Keywords: Computer science; Database management; Data mining; Artificial intelligence; Optical pattern recognition; Computer Science; Artificial Intelligence (incl. Robotics).; Data Mining and Knowledge Discovery; Database Management; Mathematical Logic and Formal Languages; Computation by Abstract Devices; Pattern Recognition